MOBILE APPLICATIONS AND ONLINE PLATFORMS IN LANGUAGE TEACHING: A CRITICAL PEDAGOGICAL ANALYSIS IN THE DIGITAL ERA - Namozova Munisa Akmaljonovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
In the contemporary digital age, it is vital for people to use mobile applications and online platforms for learning foreign languages. In this regard, modern technology makes learning more accessible, interactive, flexible and motivates students to learn by making it interesting. This study is aimed at analyzing the influence of Mobile-Assisted Language Learning (MALL) and online platforms on the acquisition of language skills. In particular, relying on scholarly literature, the paper explores both advantages and disadvantages of using these approaches to language learning.